Iron intake, supplement adherence, and perceived social support as predictors of anemia in rural Indonesia: A cross-sectional study - Yayuk Sri Rahayu; Marliana Rahma; Nita Farida (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Anemia among pregnant women remains a significant public health issue in Indonesia, particularly in Purwasari District, where 37.1% of women are anemic. Anemia may be directly influenced by social and supplementation factors, which also affect nutritional status, fetal health, and pregnancy outcomes through environmental support and the fulfillment of essential nutrient needs. This study aimed to analyze the association between social, supplementation, and nutritional factors and anemia among pregnant women in Purwasari District. A quantitative approach with a cross-sectional design was used. The sample consisted of 150 pregnant women who met the inclusion criteria of this study. Eligible participants were pregnant women aged 18–40 years in their second or third trimester. Data were analyzed using logistic regression analysis. The results showed that adequate vitamin C intake (p = 0.004; OR = 2.912), adherence to iron–folic acid (IFA) tablet consumption (p = 0.000; OR = 4.030), side effects of IFA intake (p = 0.003; OR = 3.027), and support from parents or in-laws (p = 0.026; OR = 2.563) were significantly associated with anemia in pregnancy. In conclusion, vitamin C adequacy, IFA adherence and side effects, and family support were significantly related to the occurrence of anemia among pregnant women in the Purwasari District.